MELACAK GENEOLOGI SISTEM DAN PENERAPAN MAZHAB HISAB PESANTREN KARAY GANDING SUMENEP - Ach. Mulyadi (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
The early determination of hijriyah month, can not only be done by rukyat, however it is also specified by hisab. Methodologically, those ways of expanding into idea sect, that is ru’yat sect and hisab sect. The sect of Ru’yat is made the guidance by NU, while the hisab sect developed by Muhammadiyah and mayority of pesantren maisonette, not aside from pesantren maisonette of Karay Ganding Sumenep. Its unique of practically, the hisab sect of Karay pesantren is not always same its applying with Muhammadiyah. This Matter is caused hisab sect of Karay pesantren have the separate method. This article traces system geneologis of hisab and way of its applying so that it becomes popular and a lot of people follow in Sub-Province of Sumenep. As research qualitative, this article explains about decision of Pesantren Kyai which finally use the way of hisab in determining the early month of ramadhan, and syawal and dzulhijjah by using the separate hisap method. The methodresults from reading of Pesantren Kyai to various the falak book. With examination and verification are done, finally, this method is used and followed by around society and expand through the collegiate network with special diploma.